The experience of a mentorship training program amid the COVID-19 pandemic: The views of midwifery practitioners - Hafaza Bibi Amod; Sipho Wellington Mkhize (Elsevier, 2024)
Introduction: In South Africa, clinical placement challenges in maternity units has negatively affected the clinical support of midwifery students. Evidently so, clinical support responsibilities were further side-tracked during the coronavirus pandemic, thus increasing the urgency for mentorship training. Research objective: This article explores the experiences of midwifery practitioners who participated in a mentorship training program during the Coronavirus pandemic. Method: Cycle 3 of a more extensive mixed methods study adopted a qualitative approach and a descriptive research design. To determine the outcomes of a mentorship training program, a convenient and purposive sampling technique recruited 15 midwifery practitioners to participate in two focus group sessions and five semi-structured interviews. Data collection commenced from March until June 2022, and data were analyzed using thematic content analysis. Findings: Focus group findings showed that mentorship training using an online platform was new and challenging, empowered mentorship abilities, and an investment in midwifery leadership. Findings from interviews revealed that the mentorship training program was well-structured; a valuable refresher course; improved mentorship roles and responsibilities, and has recommendations for midwifery education and practice. Discussion: Mentorship training is valuable to midwifery practitioners in South Africa, and investing in mentorship training programs empowers mentors in their roles and responsibilities. Conclusions: This study encourages collaborative partnerships and a shared responsibility between midwifery educators and practitioners through mentorship. Mentorship training could be an effective mechanism to strengthen the clinical support of midwifery students during clinical placement. A well-planned mentorship training program will likely improve the South African health care system.